2020
DOI: 10.1021/acsomega.0c01226
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Antiproliferative Evaluation, and Molecular Docking Studies of N-(3-Hydroxyindole)-Appended β-Carbolines/Tetrahydro-β-Carbolines Targeting Triple-Negative and Non-Triple-Negative Breast Cancer

Abstract: The present manuscript pertains to the design and synthesis of a series of 3-hydroxyindole-substituted β-carbolines/tetrahydro-β-carbolines with an aim to explore their antiproliferative structure−activity relationship against breast cancer. The conjugate with an optimum combination of a flexible tetrahydro-β-carboline core, a tertiary alcoholic group along with a chloro substituent on the indole ring, proved to be the most active compound. It displayed IC 50 values of 13.61 and 22.76 μM against MCF-7 (ER+) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…[124] As illustrated by the SAR, halogen atoms at C-5 position of isatin moiety favored the activity, and hybrids 83a,b (IC 50 : 13.61-22.76 µM) showed higher potency relative to tamoxifen (IC 50 : 17.71 and 69.67 µM) against the two BC cell lines. [124] Indole-phthalimide hybrid 84 (IC 50 : 0.038 µM) was highly effective against MDA-MB-231 BC cells and with the activity outperforming 5fluorouracil by 575 folds (IC 50 : 21.838 µM). [125] Subsequent evaluations illustrated that hybrid 84 may serve as apoptotic inducers via caspase-3/ 7 activation.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 97%
See 2 more Smart Citations
“…[124] As illustrated by the SAR, halogen atoms at C-5 position of isatin moiety favored the activity, and hybrids 83a,b (IC 50 : 13.61-22.76 µM) showed higher potency relative to tamoxifen (IC 50 : 17.71 and 69.67 µM) against the two BC cell lines. [124] Indole-phthalimide hybrid 84 (IC 50 : 0.038 µM) was highly effective against MDA-MB-231 BC cells and with the activity outperforming 5fluorouracil by 575 folds (IC 50 : 21.838 µM). [125] Subsequent evaluations illustrated that hybrid 84 may serve as apoptotic inducers via caspase-3/ 7 activation.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 97%
“…Indole‐γ‐carboline hybrid 81 (IC 50 : 2.99 µM) and indole‐1,2‐dihydro‐γ‐carboline hybrid 82 (IC 50 : 3.71 µM) exhibited higher activity than doxorubicin (IC 50 : 5.49 µM) against MCF‐7 cells, [ 123 ] whilst isatin‐tetrahydro‐β‐carboline carboline hybrids 83 (IC 50 : 13.61–84.38 µM) were active against MCF‐7 and MDA‐MB‐231 cell lines. [ 124 ] As illustrated by the SAR, halogen atoms at C‐5 position of isatin moiety favored the activity, and hybrids 83a,b (IC 50 : 13.61–22.76 µM) showed higher potency relative to tamoxifen (IC 50 : 17.71 and 69.67 µM) against the two BC cell lines. [ 124 ]…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been shown to act by activating various mechanisms of action, including the inhibition of DNA topoisomerases I and II, intercalation to DNA, or affecting various cancer signaling pathways [ 68 , 69 , 70 ]. Considering its high risk of cytotoxicity to normal cells, various analogues have been studied, such as the tetrahydro- β -carboline, which have shown lower cytotoxicity [ 71 , 72 , 73 ]. In addition to anticancer properties, some β -carbolines have been also reported to have antioxidant, neuroprotective, and anti-inflammatory effects [ 74 ].…”
Section: Possible Biotechnological Applicationsmentioning
confidence: 99%
“…Our research team recently showed that adding tetrahydro-bcarboline (THbC) to spiro-epoxy oxindoles resulted in 3-THbCsubstituted-3-hydroxy-oxindole with good antiproliferative effects against the MCF-7 (ER+) and MDA-MB-231 (ER) cell lines. 19 Building upon previous studies, [20][21][22] this manuscript focuses on the design, synthesis, characterization, and antiproliferative evaluation of scaffolds that incorporate substituted N-benzylated oxindoles with various secondary amines through nucleophilic ring opening of corresponding oxiranes. To compare the effect of the presence of the N-benzyl group with the free -NH group of the isatin core, the corresponding unsubstituted oxindole counterparts have also been synthesised and evaluated.…”
Section: Introductionmentioning
confidence: 99%